Thermal behavior of intelligent automotive lithium-ion batteries: Experimental study with switchable cells and reconfigurable modules. (1st December 2021) - Kleiner, Jan; Heider, Alexander; Komsiyska, Lidiya; Elger, Gordon; Endisch, Christian
Abstract: Conventional battery systems are limited regarding safety, reliability and aging performance due to fixed configurations. Intelligent battery systems are a promising solution with switches at cell level that allow adaptive reconfiguration of the system. However, the thermal influences of electronics and bypassing procedures of such systems are unknown up to now and need to be quantified. In this work, a hardware prototype of a switchable cell is realized with a 25 Ah prismatic automotive cell. The impact on the temperature on cell level for challenging 6 C discharge conditions is investigated experimentally revealing small electronics losses due to the design. Combining 12 cells in an intelligent module prototype, the thermal module behavior is investigated in terms of serial/parallel topology and effects of reconfiguration procedures. For the first time, the thermal effects in an automotive environment are tested for cells or strings being bypassed permanently during operation. Due to the thermal coupling in modules, even bypassed cells reach 40%–60% of the temperature of normally operated cells. Thereby bypassing in a parallel module is revealed to have far more thermal influence than in a serial connection. Graphical abstract: Highlights: Comprehensive intelligent battery approach with cell level sensors and actuators. Switchable cell prototype with small thermal influence on the cell at 6C. Experimental study with a reconfigurable automotive module under BEV conditions. Thermal effects of in-use reconfiguration on serial/parallel module topologies. High degree-of-freedom by cell bypassing for thermal management is revealed.